Influence of hydatidiform mole follow-up setting on postmolar gestational trophoblastic neoplasia outcomes a cohort study - Dantas, PatrÍcia Rangel Sobral [UNESP]; Maestá, Izildinha [UNESP]; Cortés-Charry, Rafael [UNESP]; Growdon, Whitfield B. [UNESP]; Braga, Antonio [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Berkowitz, Ross S. [UNESP] (My University, 2012)
OBJECTIVE: To assess the influence of hydatidiform mole (HM) management setting (reference center versus other institutions) on gestational trophoblastic neoplasia (GTN) outcomes. METHODS: This cohort study included 270 HM patients attending Botucatu Trophoblastic Diseases Center (BTDC, São Paulo State University, Brazil) between January 1990 and December 2009 (204 undergoing evacuation and entire postmolar follow-up at BTDC and 66 from other institutions [OIs]). GTN characteristics and outcomes were analyzed and compared according to HM management setting. The confounding variables assessed included age, gravidity, parity, number of abortions and HM type (complete or partial). Postmolar GTN outcomes were compared using Mann-Whitney's test, χ2 test or Fisher's exact test. RESULTS: Postmolar GTN occurred in 34 (34/204= 16.7%) BTDC patients and in 27 (27/66=40.9%) of those initially treated in other institutions. BTDC patients showed lower metastasis rate (5.8% vs. 48%, p= 0.003) and lower median FIGO (2002) score (2.00 [1.00, 3.00] vs. 4.00 [2.00, 7.00], p=0.003]. Multiagent chemotherapy to treat postmolar GTN was required in 2 BTDC cases (5.9%) and in 8 OI cases (29.6%) (p = 0.017). Median time interval between molar evacuation and chemotherapy onset was shorter among BTDC patients (7.0 [6.0, 10.0] vs. 10.0 [7.0, 16.0], p=0.040). CONCLUSION: BTDC patients showed GTN characteristics indicative of better prognosis. This underscores the importance of GTD specialist centers. © Journal of Reproductive Medicine®, Inc.
Keywords: Gestational trophoblastic neoplasia; Hydatidiform mole; Management setting